Relationship between Microcirculatory Perfusion and Arterial Elastance: A Pilot Study - Ottavia Bond; Paolo De Santis; Enrica Iesu; Federico Franchi; Jean-Louis Vincent; Jacques Creteur; Fabio Silvio Taccone; Sabino Scolletta (Critical Care Research and Practice)
Background. Arterial elastance (Ea) represents the total afterload imposed on the left ventricle, and it is largely influenced by systemic vascular resistance (SVR). Although one can expect that Ea is influenced by peripheral endothelial function, no data are available to support it in patients. The aim of this study was to investigate the relationship between Ea, SVR, and microvascular perfusion in critically ill patients undergoing the fluid challenge (FC). Methods. A prospective study in patients receiving a fluid challenge. A pulse wave analysis system (MostCare, Vygon, France) was used to estimate Ea and an incident dark field (IDF) handheld device (Braedius Medical BV, The Netherlands) to evaluate the sublingual microcirculation. Microvascular perfusion was assessed using the proportion of small-perfused vessels (PPV). Relative changes in each variable were calculated before and after FC; fluid responsiveness was defined as an increase in the cardiac index by at least 10% from baseline. Results. We studied 20 patients requiring a fluid challenge (n=10 for hypotension; n=5 for oliguria; n=3 for lactate values greater than 2 mmol/l; n=2 for tachycardia), including 12 fluid responders. There was a strong correlation between Ea and SVR (r2 = 0.75; p<0.001) and only a weak correlation between Ea and PPV at baseline (r2 = 0.22; p=0.04). Ea decreased from 1.4 [1.2–1.6] to 1.2 [1.1–1.4] mmHg/mL (p=0.01), SVR from 1207 [1006–1373] to 1073 [997–1202] dyn ∗ s/cm5 (p=0.06), and PPV from 56 [51–64] % to 59 [47–73] % (p=0.25) after fluid challenge. Changes in Ea were significantly correlated with changes in SVR, but not with changes in PPV. Conclusions. The correlation between Ea and indexes of microvascular perfusion in the sublingual region is weak. The impact of microcirculatory perfusion on the arterial load is probably limited.